Social movements and referendums from below direct democracy in the neoliberal crisis - Della Porta, Donatella 1956-; O'Connor, Francis 1984-; Portos García, Martín 1989-; Subirats Ribas, Anna ca. 20./21. Jh (Policy Press, 2017)
Social movements formed in response to austerity measures have played an increasingly important role in referendums. The book uses unique case studies to illustrate the ways the social movements have affected the referendums' dynamic and results. It also addresses the way in which participation from below has had a transformative impact